Penerapan budaya senyum, salam, sapa (3S) di MTs Ma’arif NU Kota Malang - Salafudin, Afif (Maliki Interdisciplinary Journal, 2024)
Organizational culture plays a significant role in establishing a conducive learning environment and building positive relationships between individuals in educational institutions. One of the important cultures in the educational context is the 3S Culture (Smile, Greetings, Greetings), which prioritizes friendly, polite and respectful interactions between school members. This research aims to explore the application of 3S Culture in Maarif NU Madrasah Tsanawiyah (MTs) Malang City. In this research, a qualitative approach was used with data collection techniques through observation and documentation studies. The research results show that MTs Maarif NU Malang City has succeeded in implementing 3S Culture consistently in daily life in the school environment. Smiles, greetings and greetings become part of the habit which is strengthened by consistency in daily practice, both among students and teaching staff. The implementation of 3S Culture not only creates a warm and friendly atmosphere in the school environment, but also provides a role model for students in being polite and respecting others. Furthermore, it is hoped that the 3S Culture can spread to the general public, so that students not only internalize these values at school and at home, but also in daily interactions in their social environment. This research provides an important contribution to the understanding of the implementation of 3S Culture at the Madrasah Tsanawiyah level and provides a basis for the development of better school management programs in the future. In addition, the results of this research also provide valuable insight for other educational institutions in their efforts to build a positive organizational culture and strengthen student character in the educational community.